2015
DOI: 10.1007/s00540-015-2119-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of landiolol on refractory tachyarrhythmia after total cavopulmonary connection: a retrospective, observational, cohort study

Abstract: The onset of tachyarrhythmia after the Fontan procedure (total cavopulmonary connection; TCPC) should be considered a medical emergency. Landiolol is an ultra-short-acting β1-selective blocker whose effect on tachyarrhythmia after TCPC is unclear. We evaluated the efficacy and safety of landiolol for tachyarrhythmia after TCPC. Consecutive patients undergoing TCPC were enrolled from January 2007 to December 2011. Of 435 pediatric open heart surgeries, 28 patients underwent TCPC. Of the 28 patients, 13 were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…83 Miyake et al evaluated the efficacy and safety of landiolol for tachyarrhythmia in patients undergoing the Fontan procedure (total cavopulmonary connection; TCPC). 84 The average initial dose of landiolol was 4.7 ± 2.3 μg/kg/min, without a loading dose, and this significantly reduced HR without significant blood pressure decreases. Tokunaga et al also evaluated the efficacy and safety of landiolol in the management of tachyarrhythmias after pediatric cardiac surgery.…”
Section: Role Of Prophylactic Landiolol In Pediatric Patientsmentioning
confidence: 88%
“…83 Miyake et al evaluated the efficacy and safety of landiolol for tachyarrhythmia in patients undergoing the Fontan procedure (total cavopulmonary connection; TCPC). 84 The average initial dose of landiolol was 4.7 ± 2.3 μg/kg/min, without a loading dose, and this significantly reduced HR without significant blood pressure decreases. Tokunaga et al also evaluated the efficacy and safety of landiolol in the management of tachyarrhythmias after pediatric cardiac surgery.…”
Section: Role Of Prophylactic Landiolol In Pediatric Patientsmentioning
confidence: 88%
“…In the present study, landiolol administration begins at a dose of 1 mg/kg/min, and the dose is increased by 1 mg/kg/min every 15 to 20 min to a maximum dose of 10 mg/kg/min. This regimen is based on the following information: most previous clinical studies reported that doses of 1-10 mg/kg/min landiolol with dose adjustment were efficacious and tolerable in pediatric patients [6,[18][19][20][21][22][23]; a retrospective analysis on 12 pediatric patients indicated that higher doses (initial loading dose of 40 mg/kg/ min, followed by maintenance dose of 10-40 mg/kg/min) produced excessive bradycardic responses, and the authors recommended starting with a lower dosage beginning at 3-5 mg/kg/min with monitoring of hemodynamics [23]. The present study will demonstrate that our dosing strategy is appropriate and will provide a standard dosing schedule that assures the efficacy and safety of landiolol for the treatment of pediatric tachyarrhythmia patients under monitoring of hemodynamic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…slow onset of action. Practically, adenosine, amiodarone, and landiolol [18][19][20][21][22][23], which are all intravenously administered, have been used to control heart rate in pediatric tachyarrhythmias in Japan to date. In fact, landiolol is cited in the guideline for diagnosis and therapy of pediatric arrhythmia as one of the agents that can be used for treating postoperative tachyarrhythmia in the pediatric population [6].…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 96 records retrieved by the systematic search in PubMed and EMBASE, 15 studies met the inclusion criteria and included a total of 1744 children (Table 5). 78,[94][95][96][97][98][99][100][101][102][103][104][105][106][107] All studies were single centre. There were nine retrospective cohort studies and one retrospective case-control study.…”
Section: Antiarrhythmicsmentioning
confidence: 99%
“…100 Landiolol shows promise for the treatment of tachyarrhythmias with rare adverse events. [103][104][105][106] Dexmedetomidine, while typically used as a sedative, has also been studied in preventing tachyarrhythmias. Evidence is conflicting regarding its efficacy for treating tachyarrhythmias.…”
Section: Antiarrhythmicsmentioning
confidence: 99%